Meneropong Efek Domino Pendidikan Karakter Imam Eli dan Samuel dalam Perjanjian Lama - Tambunan, Tamara Maria Geraldine; Pakpahan, Gernaida Krisna R. (STIPAK Malang, 2024)
This study explores the parenting styles of Priest Eli and Samuel in the context of the Old Testament and their relevance to contemporary child-rearing practices. Using a qualitative method with a narrative approach and library research, this study examines biblical narratives that depict the interactions and parenting provided by Eli and Samuel to their children. The results show that Priest Eli's failure to discipline his children, Hophni and Phinehas, led to severe consequences in their lives and their service before God. Although Samuel succeeded as a respected spiritual leader, he faced similar failures in raising his children, Joel and Abijah. This study highlights the importance of balanced discipline and affection in parenting and the unique challenges faced by the families of God's servants. The findings are expected to contribute significantly to developing a more effective and comprehensive character education curriculum and inspire educators and policymakers to design educational strategies that shape young generations with strong moral and ethical values.